2015
DOI: 10.1007/s11869-015-0369-9
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of particulate matter concentration profile in an opencast copper mine in India using an artificial neural network model

Abstract: Springer Science+Business Media Dordrecht Particulate matter (PM) is a major pollutant in and around opencast mine areas. The problem of degradation of air quality due to opencast mine is more severe than those in underground mine. Prediction of dust concentration must be known to implement control strategies and techniques to control air quality degradation in the workplace environment. Limited studies have reported the dispersion profile and travel time of PM between the benches inside the mine. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Gurjar et al (2010) have suggested the exposure to PM 2.5 is a more severe problem in the urban area as compared to the rural area. PM 2.5 pollution is defined by both quantitative and qualitative measurements of a number of activities conducted by different groups at particular places for short time intervals (Gautam et al 2016a, b;Patra et al 2016b;Gautam and Patra 2015). Moreover, most of the research work on PM 2.5 has paid more attention to urban areas than to rural areas for the exploration of the sources and adverse effects (Gautam et al 2016b;Lin et al 2015a;Vela et al 2015;Kumar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Gurjar et al (2010) have suggested the exposure to PM 2.5 is a more severe problem in the urban area as compared to the rural area. PM 2.5 pollution is defined by both quantitative and qualitative measurements of a number of activities conducted by different groups at particular places for short time intervals (Gautam et al 2016a, b;Patra et al 2016b;Gautam and Patra 2015). Moreover, most of the research work on PM 2.5 has paid more attention to urban areas than to rural areas for the exploration of the sources and adverse effects (Gautam et al 2016b;Lin et al 2015a;Vela et al 2015;Kumar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic behaviour of particulate emission can be studied by various methods such as artificial neural networks (ANNs), regression analysis, classification and regression tree (CART), ARIMA modelling, rescaling (R/S), goodness‐fit‐test comprising chi‐square statistic, Kolmogorov–Smirnov statistics, Anderson–Darling statistics, linear unbiased estimates, Monte‐Carlo maximum likelihood estimator (MCMLE), correlation analyses, and power spectrum analyses and so forth. (Diaz‐Robles et al, 2008; Gautam, Patra, et al, 2021; Liu, 2017; Patra et al, 2016; Roy, 2021; Taheri et al, 2016). All the statistical methods used are for finding correlation between meteorological parameters and pollutant concentrations, as well as to evaluate the amount of persistence or randomness in the time series (de Medrano et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter present in the gases poses an immediate hazard to health. A study on the dispersion of particulate matter in and around mines and the duration of exposure to these PMs was conducted by Patra et al (2015) [21].An artificial neural network (ANN) study was done in the premises of the Hindustan Coal Limited (HCL), India. They studied the effect of wind speed, wind direction, ambient temperature, relative humidity, and PM concentration.…”
Section: Introductionmentioning
confidence: 99%